Methodological adjustments in a computer engineering course to enhance social responsability - Contreras, Marcela Varas; Albornoz, Jorge Maluenda (2017 36th International Conference of the Chilean Computer Science Society (SCCC), 2017)
The present article is an experience of implementation in the classroom of methodologies related to the development of competences of students of Computer Engineering associated with Socially Responsible professional practice. The experience incorporated elements of Service- Learning, foundations of CDIO and social profitability to reformulate the regular work of the subject. The results observed on the 14 students allow us to think that the strategies used have a favorable impact on the development of Social Responsibility, specifically, on the Intentions of socially responsible behavior. In addition, positive impacts on students' motivation and the linking of professional practice with socially responsible ethics were observed